2018
DOI: 10.1289/ehp2387
|View full text |Cite|
|
Sign up to set email alerts
|

Hydroxylated Polybrominated Biphenyl Ethers Exert Estrogenic Effects via Non-Genomic G Protein–Coupled Estrogen Receptor Mediated Pathways

Abstract: Background:Numerous studies have indicated the estrogenic effects of polybrominated diphenyl ethers (PBDEs) and hydroxylated PBDEs (OH-PBDEs). However, the previous mechanistic studies focused on their estrogenic effects through genomic transcriptional activation of estrogen receptors.Objective:The present study aimed to investigate the estrogenic effects of PBDEs and OH-PBDEs via nongenomic G protein–coupled estrogen receptor (GPER) pathways.Methods:The binding affinities of 12 PBDEs and 18 OH-PBDEs with GPER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…In addition to antiestrogens, various nonselective GPER1 agonists have been identified: these include natural products like hydroxytyrosol and oleuropein, as well as phytoestrogens, such as coumestrol, and the endocrine-disrupting compounds Bisphenol A (BPA) ( Figure 2) (20-22). Additional studies have identified synthetic polybrominated diphenyl ethers (PBDEs) and hydroxylated PBDEs as potential GPER1 ligands; however, these compounds likely exhibit no selective activity (23).…”
Section: Current Ligands For the Modulation Of Gper1 Signalingmentioning
confidence: 99%
“…In addition to antiestrogens, various nonselective GPER1 agonists have been identified: these include natural products like hydroxytyrosol and oleuropein, as well as phytoestrogens, such as coumestrol, and the endocrine-disrupting compounds Bisphenol A (BPA) ( Figure 2) (20-22). Additional studies have identified synthetic polybrominated diphenyl ethers (PBDEs) and hydroxylated PBDEs as potential GPER1 ligands; however, these compounds likely exhibit no selective activity (23).…”
Section: Current Ligands For the Modulation Of Gper1 Signalingmentioning
confidence: 99%
“…Nonetheless, the systematic comparison between models with lipid-adjusted and wet-basis biomarkers did not yield substantial modifications of risk estimates, thus ruling out more complex underlying associations. We used the parent forms of PBDEs as biomarkers of internal exposure, while little is known about the potential adverse health effects of their hydroxylated forms as products of biotransformation metabolism, which have shown exert estrogenic effects [37]. Thus, one hypothesis to be deeper investigated for explaining the observed reverse associations would be the potential protective effect of adipose tissue by sequestrating the parent compounds and more biologically active hydroxylated metabolites, preventing the release into circulation and thus the exposure of carcinogenic cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…PBDEs are used as flame retardants, electrical equipment coating, construction materials, textiles, and furniture padding [39,40]. PBDEs encompass a large umbrella of compounds that have a relative binding affinity range of 1.3-20 to ERs [41].…”
Section: Xenoestrogens: Synthetic Industrial Chemicalsmentioning
confidence: 99%